Natural Killer Cells - Aribi, Mourad (IntechOpen, 2017)
The book Natural Killer Cells is the result of a collective work that addresses in a clear and comprehensive way for readers and through as many sensuous details as possible, the most and various fundamental aspects of natural killer cells, as well as their clinical applications in cancer immunotherapy. This book will serve as an invaluable resource and pedagogical support for clinicians, researchers, basic scientists, immunology and immunopathology lecturers, as well as for students in biology and medicine, especially the ones with an advanced understanding of immunology.